Geospatial delineation and mapping of groundwater potential in Embu County, Kenya - Chepchumba, Mary Christine; Raude, James M.; Sang, Joseph K. (Acque Sotterranee - Italian Journal of Groundwater, 2019)
Integration of Remote Sensing (RS) and the Geographical Information System (GIS) approaches in the field of groundwater resources management is a breakthrough. The RS and GIS geospatial approaches can enhance the assessment, monitoring, and conservation of groundwater resources. In this study, RS and GIS geospatial techniques were applied with the aim of identifying groundwater potential zones in Embu County, Kenya, based on selected multi influencing factors. Lineament layer was obtained by processing Landsat 8 ETM+ image using Principal Component Analysis in ENVIÂ®4.7 and automatic extraction from Principal Component Image using the LINE module in Geomatica software. The resultant groundwater potential map showed that approximately 78% of the total area ranged from â€˜high’ to â€˜very high’ zones indicating that almost half of the study area has good groundwater potential. About 20% showed moderate potential while only 2% fell under the low potential zone. The proposed study approach can be used as a new way of modeling geospatial data for identification and mapping of groundwater potential zones. The study findings are useful to first-hand information planners and local authorities for assessment, planning, management and administration of groundwater resources in Embu County.